Transcoronary Platelet Thromboxane A2 Formation without Platelet Trapping in Patients with Coronary Stenosis - Effect of Sulphinpyrazone Treatment - Cortellaro, M; Boschetti, C; Antoniazzi, V; Moreo, G; Repetto, S; Verna, E; Boscarini, M; Limido, A; Binaghi, G; Polli, E E (Thrombosis and Haemostasis, 1983)
Platelet count, and plasma thromboxane B2 (TXB2) and circulating platelet aggregates (CPA) were determined in the coronary sinus (CS), aortic bulb (AO) and cubital vein (V) in 21 patients with stable angina and in 6 control subjects before and after atrial pacing (AP). TXB2 measurements were repeated before and after AP in 6 of the 21 angina patients after 15 days’ sulphinpyrazone treatment. Platelet count and CPA ratio were similar in angina patients and controls at all three sampling sites and were unchanged at AP peak. In the controls, basal TXB2 values in CS, AO and V were not significantly different and were unchanged at AP peak. In the angina patients compared with the controls, basal TXB2 values in the AO, CS and V were not significantly different whereas the CS/AO TBX2 ratio was significantly higher; at AP-induced ischaemia, CS TXB2 was significantly increased and the CS/AO TXB2 ratio was increased. A weak but significant direct correlation was found between CS/ AO TXB2 ratio and coronary score. Sulphinpyrazone treatment reduced CSTXB2 levels at rest and after AP, but not the ischaemic threshold at AP.
Keywords: Thromboxane A2; Transcoronary platelet activity; Stable angina; Sulphinpyrazone